AN EPIDEMIOLOGICAL STUDY OF SOCIAL FACTORS ASSOCIATED WITH MATERNAL MORTALITY IN A COMMUNITY DEVELOPMENT BLOCK OF MADHYA PRADESH - Joshi, K P; Kushwah, S S (Indian Journal of Community Health, 2011)
Background- India is among those countries which have very high Maternal Mortality Rate (301/100,000 live birth) .In Madhya Pradesh MMR is much higher (379/100,000/live birth). About 78,000 women die each year due to pregnancy related causes. Social factors play important role in maternal morbidity and mortality. Research Question –What is the magnitude of Maternal Mortality and its social determinants in a Community Development Block of District Satna (MP.). Objective– To assess the magnitude of Maternal Mortality and its social determinants. Study Design-Retrospective epidemiological study. Setting and Participants - The subjects included were female deaths of reproductive age group (15-45 years) of a Community Development Block Satna (MP.). Methodology- The data were collected from available health records, by house to house survey and verbal autopsy in study area. Results - A total of 27 maternal deaths were gathered from deferent sources during one year study period, thus giving, MMR of 550/100,000 live birth. Maximum 24 maternal deaths (88.8%) occurred in the age group of 18-30years.Around 55% maternal deaths took place in low socio economic group. Around 44.44% mothers did not take any antenatal care during their pregnancies. Around twelve maternal deaths (44%) were due to direct obstetrical causes and remaining 15 maternal deaths (54%) were due to indirect causes. The reason in 62.96% mothers for non- availing hospital treatment were financial constraints, ignorance, illiteracy, late decision, male dominance in family matters.